2013
DOI: 10.3390/pharmaceutics5010179
|View full text |Cite
|
Sign up to set email alerts
|

Drug Adverse Event Detection in Health Plan Data Using the Gamma Poisson Shrinker and Comparison to the Tree-based Scan Statistic

Abstract: Background: Drug adverse event (AE) signal detection using the Gamma Poisson Shrinker (GPS) is commonly applied in spontaneous reporting. AE signal detection using large observational health plan databases can expand medication safety surveillance. Methods: Using data from nine health plans, we conducted a pilot study to evaluate the implementation and findings of the GPS approach for two antifungal drugs, terbinafine and itraconazole, and two diabetes drugs, pioglitazone and rosiglitazone. We evaluated 1676 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Brown et al compared Poisson tree-based scan statistics to disproportionality analyses and found reasonable concordance with the two approaches. 6 In other words, when the methods are applied to the same empirical dataset, both techniques showed similar detection capability although no formal power studies were performed for this comparison.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown et al compared Poisson tree-based scan statistics to disproportionality analyses and found reasonable concordance with the two approaches. 6 In other words, when the methods are applied to the same empirical dataset, both techniques showed similar detection capability although no formal power studies were performed for this comparison.…”
Section: Introductionmentioning
confidence: 99%
“…3 Here, we focus on one data mining method that leverages these longitudinal data: the tree-based scan statistic. 4 Previously, it has been shown to perform well in postmarket medical product safety settings, [5][6][7] and is planned to monitor nine-valent human papillomavirus vaccine exposure in the FDA's Sentinel System. 8 Additionally, the United States Centers for Disease Control and Prevention have indicated that they intend to use the method in their vaccine monitoring system, the Vaccine Safety Datalink.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on one data mining method that leverages these longitudinal data: the tree-based scan statistic [ 4 ]. Previously, it has been shown to perform well in postmarket medical product safety settings [ 5 6 7 ], and is planned to monitor nine-valent human papillomavirus vaccine exposure in the FDA’s Sentinel System [ 8 ]. Additionally, the United States Centers for Disease Control and Prevention have indicated that they intend to use the method in their vaccine monitoring system, the Vaccine Safety Datalink [ 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nelson et al’s paper does not formally compare methods. Brown et al compared Poisson tree-based scan statistics to disproportionality analyses and found reasonable concordance with the two approaches [ 6 ]. In other words, when the methods are applied to the same empirical dataset, both techniques showed similar detection capability although no formal power studies were performed for this comparison.…”
Section: Introductionmentioning
confidence: 99%
“…We studied the safety of Gardasil, hereafter called quadrivalent human papillomavirus vaccine (4vHPV), applying a self-controlled tree-temporal scan statistic data-mining method ( 22 24 ) to health insurance claims data for signal detection. The method allows a wide variety of unsuspected but potential adverse reactions and a range of potential postvaccination periods of increased risk (“risk windows”) to be simultaneously evaluated, adjusting for the multiple testing involved.…”
mentioning
confidence: 99%